Ferroptosis and hyperoxic lung injury: insights into pathophysiology and treatment approaches - Zhou, Xiaoqiong; Tian, Lei; Xiong, Wenyan; Li, Yulan; Liu, Qian (Frontiers in Pharmacology, 2025)
Hyperoxia therapy is a critical clinical intervention for both acute and chronic illnesses. However, prolonged exposure to high-concentration oxygen can cause lung injury. The mechanisms of hyperoxic lung injury (HLI) remain incompletely understood, and current treatment options are limited. Improving the safety of hyperoxia therapy has thus become an urgent priority. Ferroptosis, a novel form of regulated cell death characterized by iron accumulation and excessive lipid peroxidation, has been implicated in the pathogenesis of HLI, including diffuse alveolar damage, vascular endothelial injury, and bronchopulmonary dysplasia. In this review, we analyze the latest findings on ferroptosis and therapeutic strategies for HLI. Our aim is to provide new insights for the treatment of HLI and to facilitate the translation of these findings from bench to bedside.